1994
DOI: 10.1136/gut.35.11.1536
|View full text |Cite
|
Sign up to set email alerts
|

Primary peristalsis is the major acid clearance mechanism in reflux patients.

Abstract: This study examined the clearance of gastric acid from the oesophagus in ambulant patients with gastrooesophageal reflux. Eighteen patients with proved reflux disease were studied, nine with (group 1) and nine without (group 2) endoscopic oesophagitis. Oesophageal pressure and pH were recorded over 24 hours. Pressures were measured by a probe with five sensors: a 5 cm long sensor in the lower oesophageal sphincter, three sensors in the body of the oesophagus, and one at the pharynx to detect swallowing. Oesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 16 publications
5
27
0
1
Order By: Relevance
“…Acid clearance is a two-step process: swallowing and primary peristalsis aids in the transport of alkaline saliva to the distal esophagus, whilst secondary peristalsis is necessary for the clearance of the bulk of the refluxate. A longer delay from the onset of the reflux event to the initial clearing event has been shown in patients with reflux disease compared to controls [44]. Barham et al [45] reported even longer acid clearance time in patients with reflux strictures.…”
Section: Esophageal Dysmotilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Acid clearance is a two-step process: swallowing and primary peristalsis aids in the transport of alkaline saliva to the distal esophagus, whilst secondary peristalsis is necessary for the clearance of the bulk of the refluxate. A longer delay from the onset of the reflux event to the initial clearing event has been shown in patients with reflux disease compared to controls [44]. Barham et al [45] reported even longer acid clearance time in patients with reflux strictures.…”
Section: Esophageal Dysmotilitymentioning
confidence: 98%
“…Primary peristalsis is the initial response to acid reflux in normal subjects when in the upright position, whereas secondary peristalsis is the initial clearing event when subjects are supine and asleep [22, 23, 44, 46, 47]. Impairment of primary peristalsis is evident by the increased time to onset of the peristaltic response, fewer number of peristaltic events, increased time interval between peristaltic events, low-amplitude peristaltic contractions, simultaneous contractions and a lower number of complete peristaltic sequences in reflux patients compared to healthy subjects [45, 46, 48].…”
Section: Esophageal Dysmotilitymentioning
confidence: 99%
“…In studies on peristaltic wave efficacy it was found that the peristaltic wave is effective, i.e. it pushes the food bolus towards the stomach, if the contraction amplitude in the proximal part is not lower than 16 mmHg, and in the distal part 30 mmHg [22,23]. In a considerable number of patients with reflux disease the oesophageal motility is impaired [22,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…it pushes the food bolus towards the stomach, if the contraction amplitude in the proximal part is not lower than 16 mmHg, and in the distal part 30 mmHg [22,23]. In a considerable number of patients with reflux disease the oesophageal motility is impaired [22,24,25]. Motility impairment is present in about 25% of patients with mild GERD and in about 50% of patients with severe form of the disease [12,26].…”
Section: Discussionmentioning
confidence: 99%
“…In this event, esophageal acid clearance in normal subjects usually restores a normal pH within 3-5 minutes. 5 First, esophageal peristalsis clears the majority of the acid ("volume clearance"), 6 and secondly bicarbonate-containing saliva neutralizes any remaining acid by "chemical clearance". 7 Both of these mechanisms are believed to be activated and regulated via reflexes triggered by esophageal acidification and distension.…”
Section: Introductionmentioning
confidence: 99%